A Natural Resource Theory of U.S. Crop Insurance Contract Choice. (7th August 2013) - Du, Xiaodong; Hennessy, David A.; Feng, Hongli
Abstract: A large variety of subsidized crop insurance products are available to U.S. crop growers. Distinct and perhaps puzzling patterns in the choices of insurance products and coverage levels can be discerned. Where production conditions are better and yields are less risky then ( a ) higher insurance coverage levels are chosen; and ( b ) revenue insurance is preferred over yield insurance. Also, ( c ) the extent of preference for revenue insurance is stronger in more productive areas. Assuming, as many do, that growers seek to maximize subsidy transfers, point ( a ) can be explained by the interaction between yield technology and natural resource endowments. Points ( b ) and ( c ) can be explained by location in conjunction with the "natural hedge" and a contract design bias in how revenue insurance guarantees are computed. Empirical study of Risk Management Agency data on corn, soybean, and wheat yields, and insurance contract choices lend support to our model inferences.